A nomogram to predict the risk of colorectal anastomotic leakage combining inflammatory-nutritional and abdominal aorta calcium index - Zhang, Zhaoxiong; Sun, Weilin; Wang, Jun; Deng, Yuanlin; Yan, Yongjia; Li, Dong; Fu, Weihua (Frontiers in Surgery, 2023)
Background Anastomotic leakage is a serious complication after colorectal cancer surgery, which affects the quality of life and the prognosis. This study aims to create a novel nomogram to predict the risk of anastomotic leakage for patients with colorectal cancer based on the preoperative inflammatory-nutritional index and abdominal aorta calcium index. Methods 292 patients at Tianjin Medical University General Hospital (Tianjin, China) from January 2018 to October 2021 who underwent colorectal cancer surgery with a primary anastomosis were retrospectively reviewed. A nomogram was constructed based on the results of multivariate logistic regression model. The calibration curves and receiver operating characteristic curves were used to verify the efficacy of the nomogram. Results Univariate and multivariate analyses showed that tumor location (P = 0.002), preoperative albumin (P = 0.006), preoperative lymphocyte (P = 0.035), preoperative neutrophil to lymphocyte ratio (P = 0.024), and superior mesenteric artery calcium volumes score (P = 0.004) were identified as the independent risk factors for postoperative anastomotic leakage in patients with colorectal carcinoma. A nomogram was constructed based on the results of the multivariate analysis, and the C-index of the calibration curves was 0.913 (95%CI: 0.870–0.957) in the training cohort and 0.840 (95%CI: 0.753–0.927) in the validation cohort. Conclusion The nomogram, combining basic variables, inflammatory-nutritional index and abdominal aorta calcium index, could effectively predict the possibility of postoperative anastomotic leakage for patients with colorectal cancer, which could guide surgeons to carry out the appropriate treatment for the prevention of anastomotic leakage.